Pengembangan Bahan Ajar Matakuliah Dayung Berbasis Blended Learning untuk Mahasiswa PJKR - Damaris Marlissa; Wasis Djoko Dwiyogo; Supriyadi Supriyadi (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The purpose of this research and development is to create a teaching material creation based on blended learning (face to face, offline, and online) for rowing teaching materials. The development of teaching materials for the blended learning-based rowing course, the researchers used a research method based on blended learning for problem-solving learning outcomes. The researcher obtained the results from the effectiveness test at the three meetings the researcher had conducted. Effectiveness test data: in the first meeting: the average grade grade of students obtained the letter A (89.63%). The second meeting: the average grade grade of the students was obtained by the letter A (90.38%). In the third meeting: the average grade score of the students was obtained